1998
DOI: 10.1161/01.res.83.7.721
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for Prostacyclin in Nitric Oxide–Induced Ocular Vasorelaxation in the Piglet

Abstract: —We studied the mechanisms of retinal and choroidal vasorelaxation elicited by nitric oxide (NO) using piglet eyes. The NO donors sodium nitroprusside (SNP) and diethylamine-NONOate caused comparable concentration–dependent relaxation that was partially (≈40%) attenuated by the guanylate cyclase inhibitors methylene blue and LY83583 and reduced to a lesser extent (≈25%) by the inhibitor of cGMP–dependent kinase, KT 5823. In contrast, NO-induced dilatation (by NO donors and endogenous NO after stimulation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…At the same time, PGI2 regulates the endothelial function via crosstalk with endothelial nitric oxide synthase (eNOS) 57) . This indicates that NO activates PGI2 synthase and increases PGI2 production 58) . It is believed that EPA-derived PGI3 is also involved in NO production.…”
Section: Effects Of Pgi2 and Pgi3 On The Vascular Tonementioning
confidence: 94%
“…At the same time, PGI2 regulates the endothelial function via crosstalk with endothelial nitric oxide synthase (eNOS) 57) . This indicates that NO activates PGI2 synthase and increases PGI2 production 58) . It is believed that EPA-derived PGI3 is also involved in NO production.…”
Section: Effects Of Pgi2 and Pgi3 On The Vascular Tonementioning
confidence: 94%
“…Prostacyclin is a vasoactive prostaglandin produced by vascular cells that induce vasodilation in vivo at physiologic concentrations (19,20). PGI2 is also reported to increase vascular permeability (21,22), promote pericyte relaxation (20), and mediate nitric oxideinduced (NO-induced) ocular vasorelaxation (19).…”
mentioning
confidence: 99%
“…PGI2 is also reported to increase vascular permeability (21,22), promote pericyte relaxation (20), and mediate nitric oxideinduced (NO-induced) ocular vasorelaxation (19). Elevated glucose concentrations stimulate PGI2 secretion in human retinal pericytes (RPCs) (23), and acutely elevated blood glucose increases retinal blood flow (1).…”
mentioning
confidence: 99%
“…These results suggest that both NO and PGs appear to be important in the regulatory mechanisms of retinal / choroidal hemodynamics. However, the vasorelaxant effects of NO on retinal / choroidal vasculature may be explained by PGI 2 released from endothelial cells (9,10). In preliminary studies, we also found that, NO-mediated vasodilation of retinal arterioles was largely attenuated by indomethacin, an inhibitor of cyclooxygenase, in rats (11,12).…”
Section: Introductionmentioning
confidence: 82%